Motif Siswa memiliki Smartphone dan Penggunaannya - Jamilah Aini Nasution; Neviyarni Suhaili; Alizamar Alizamar (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2017)
In July 2012, it's registered that 58% of 47 million people who have smartphone in Indonesian is dominated by teenager aged 14 until 17 years (result of research by Nielsen). Students should be use the smartphone appropriate with function to pointing students on a positive thing, but students indicate that they still use smartphone for a negative thing. This study aimed to analyze and to describe about motives of students to choose smartphone and the use of smartphone by students SMA Pembangunan Laboratorium UNP Padang. This research is a quantitative study with descriptive approach. The population is all students who have a smartphone as many as 227 students. Sample as many as 145 students. Instrument used is the scale of motive students have a smartphone and the use of smartphone. The results of data analysis showed that: (1) the level of motive students have a smartphone in SMA Pembangunan Laboratorium UNP Padang at the high category, and (2) the level of use smartphone by students SMA Pembangunan Laboratorium UNP Padang also at the high category.